The Association Of Serum Cortisol Level With Microalbuminuria In Patients With Type 2 Diabetes And Prediabetes - Zhang, Xiaodan (Int J Med Sci, 2020)
Whether cortisol secretion is linked with microalbuminuria remains undefined. We aimed to investigate the relationship between serum cortisol levels and the presence of microalbuminuria in patients with type 2 diabetes (T2DM) and prediabetes. A cross-sectional study was conducted with 211 patients with T2DM or prediabetes. Serum cortisol was measured at 8:00 h, 16:00 h, and 0:00 h. The level and circadian rhythm of ACTH were also evaluated. Urine excretion of albumin was measured. Patients were subdivided into microalbuminuria (MAU) group (n= 120) and normoalbuminuria (NAU) group (n = 91) according to the status of microalbuminuria. Levels of serum cortisol (8:00 h: 426.9 ± 155.0 nmol/; 16:00 h: 303.7 ± 144.7 nmol/L) were significantly higher in MAU group than in NAU group (8:00 h: 370.2 ±130.6 nmol/L, P = 0.004; 16:00 h: 234.7 ± 120.2 nmol/L, P = 0.001). After adjustment for multiple factors, the correlation between cortisol levels (both at 8:00 h (P = 0.005) and at 16:00 h (P = 0.001)) and microalbuminuria remained consistent and significant. Higher levels of cortisol (cut-off value: 390.5 nmol/L at 8:00 h, 203.5 nmol/L at 16:00 h) help to detect the development of microalbuminuria. Serum cortisol secretion is associated with the presence of microalbuminuria in patients with T2DM and patients with prediabetes. Higher levels of cortisol, even in the normal range, may be related with the development of microalbuminuria.